If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-5x + -7) + -7x = 0 Reorder the terms: 4(-7 + -5x) + -7x = 0 (-7 * 4 + -5x * 4) + -7x = 0 (-28 + -20x) + -7x = 0 Combine like terms: -20x + -7x = -27x -28 + -27x = 0 Solving -28 + -27x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -27x = 0 + 28 Combine like terms: -28 + 28 = 0 0 + -27x = 0 + 28 -27x = 0 + 28 Combine like terms: 0 + 28 = 28 -27x = 28 Divide each side by '-27'. x = -1.037037037 Simplifying x = -1.037037037
| a-b=36 | | -6(-7a-6)= | | 2x+1*x+1=18 | | 2x+33=x+30 | | f(x)=2x^2+6x-18 | | 3x(x+3)=6-(7x+2) | | 4x-1=-2(x-1) | | Y=2x^2+8x-30 | | 2x+1+x+1=18 | | 2-2(4+9a)= | | -6+9(x-1)=16x+2-7x | | 9+2i=0 | | 7(x+4)-3=29-2x-4+9x | | -28=x-3.7 | | 200/x=3x | | 1/4-x=3/x | | (d^3+d^2-4d)y=0 | | 4(b+3)=9 | | 12x+11=156 | | 28y+4x=4 | | -3p/2;0 | | x^2=16y-32 | | 25=18-2y | | -2(5x-9)+7=-10X+25 | | -26=9+5x | | 7x(2)=63 | | (3/5)2 | | 0.25x=(9/365)x | | x^4-12x^3+36x^2-20x+3=0 | | x+(x*.12)=765 | | I-(1+7x)-6(-7-x)=36 | | 15/20=3/x |